Reduced Lateralization of Attention in Action Video Game Players - Li, Yu; Jin, Xiaohong; Wang, Yuanyuan; Niu, Dun (Frontiers in Psychology, 2019)
There is increasing evidence that action video game players (AVGPs) possess superior performance in various tasks, especially those measuring attentional abilities. The current study aimed to examine the lateralization of attentional components in AVGPs. Twenty-nine AVGPs and twenty-six non-AVG players (NAVGPs) were recruited based on their frequency and intensity of playing action video games in the last six months. A lateralized attentional network test was used to measure the lateralization of attentional components in the two groups. The results showed that AVGPs exhibited more comparable performance in the left and right hemispheres for reorienting and executive components. However, NAVGPs exhibited a significant difference between the two hemispheres for the two components. The findings indicate that AVG playing is closely associated with reduced lateralization of attentional networks.